Criminal Economy in Veracruz and the Totonacapan Region, Mexico, 1998-2018 - Alvear-Galindo, Ma. Guadalupe; Giraldo-Durán, Angélica; Ramírez-Gutiérrez, Sandy E.; Mtro Valadez Hernández (Sociedad y Economía, 2022)
The article aims to identify the main elements of the criminal economy in Veracruz and the Totonacapan region (Mexico). To that end, it explores how illegal economic activities have joined sectors of legal capital, considering corruption and the exercise of violence as central mechanisms. To this end, an analytical review of bibliographic, hemerographic, and statistical sources is carried out. The study argues that: 1) the presence of strategic natural resources, economic precariousness, and political circumstances conducive to corruption are conditions of possibility for the criminal economy in Veracruz and Totonacapan; 2) the illegal trafficking of goods is a central source of financing for organized crime, an incentive for territorial control and a propitiator of violence in the case studied; 3) fuel theft is a paradigmatic example of the functioning of the criminal economy in this territory.